Optimal Extraction of Ocimum basilicum Essential Oil by Association of Ultrasound and Hydrodistillation and Its Potential as a Biopesticide Against a Major Stored Grains Pest - Eridiane da Silva Moura; Lêda Rita D’Antonino Faroni; Fernanda Fernandes Heleno; Alessandra Aparecida Zinato Rodrigues; Lucas Henrique Figueiredo Prates; Maria Eliana Lopes Ribeiro de Queiroz (Molecules, 2020)
The essential oil of basil (Ocimum basilicum) has significant biological activity against insect pests and can be extracted through various techniques. This work aimed to optimize and validate the extraction process of the essential oil of O. basilicum submitted to different drying temperatures of the leaves and extracted by the combination of a Clevenger method and ultrasound. The biological activity of the extracted oil under different conditions was evaluated for potential control of Sitophilus zeamais. The extraction method was optimized according to the sonication time by ultrasound (0, 8, 19, 31 and 38 min) and hydrodistillation (20, 30, 45, 60 and 70 min) and drying temperature (20, 30, 45, 60 and 70 °C). The bioactivity of the essential oil was assessed against adults of S. zeamais and the effects of each variable and its interactions on the mortality of the insects were evaluated. The best yield of essential oil was obtained with the longest sonication and hydrodistillation times and the lowest drying temperature of leaves. Higher toxicity of the essential oil against S. zeamais was obtained by the use of ultrasound for its extraction. The identification and the relative percentage of the compounds of the essential oil were performed with a gas chromatograph coupled to a mass selective detector. The performance of the method was assessed by studying selectivity, linearity, limits of detection (LOD) and quantification (LOQ), precision and accuracy. The LOD and LOQ values for linalool were 2.19 and 6.62 µg mL−1 and for estragole 2.001 and 6.063 µg mL−1, respectively. The coefficients of determination (R2) were >0.99. The average recoveries ranged between 71 and 106%, with coefficient of variation ≤6.4%.